Perceived barriers to reaching equity in effective access to diagnosis and treatment for women with breast cancer in Chile - Carla Campaña; Báltica Cabieses; Alexandra Obach; Francisca Vezzani (Humanities & Social Sciences Communications)
Abstract Globally, it has been reported inequities in breast cancer effective access to health care. The objective of this study was to explore perceived inequities in access to effective diagnosis and treatment in women with breast cancer according to Tanahashi model and social determinants of health model. An exploratory case study, under a qualitative paradigm, was conducted. Theoretical sampling guided the selection of diverse participant profiles, comprising breast cancer patients, healthcare professionals and a civil society leader. The strategies for the recruitment process included social networks, civil society organizations, health professionals, and the snowball technique. Online semi-structured interviews were conducted. Interviews were transcribed, anonymized, and coded using ATLAS.Ti for deductive thematic analysis. Barriers to effective healthcare access were identified in all components of Tanahashi model. Accessibility and acceptability were the components with most perceived barriers. From the determinants of health model, a woman from the public health system, with low income, under 30 or over 40, and residing in a different region from the metropolitan region faces more barriers to access to an effective healthcare. The main barriers were for the high centralisation of healthcare in Chile, not integrated health system network, misinformation to the patient, and non-humanized healthcare. The results of this study offer a comprehensive exploration of perceived barriers to effective breast cancer diagnosis and treatment in Chile, using a qualitative approach incorporating diverse perspectives. Findings underscore significant systemic challenges across Tanahashi’s model components, impacting the overall care experience. The study reveals structural inequities hindering healthcare access, reflecting global patterns in fragmented health systems.